Removal of Direct Yellow 12 from Water Samples by Cloud Point Extraction Using Triton X-100 as Nonionic Surfactant - Shahnaz Abedi; Farzin Nekouei (E-Journal of Chemistry)
A surfactant mediated cloud point extraction (CPE) procedure has been developed to remove color from wastewater containing direct yellow 12 (Chrysophenine G), using triton x-100 (TX-100) as nonionic surfactant. The effects of the concentration of the surfactant, pH, temperature and salt concentration on the different concentration of dye have been studied and optimum conditions were obtained for the removal of direct yellow 12 (DY 12). The concentration of DY 12 in the dilute phase was measured using UV-Vis spectrophotometer. It was found that the separation of phases was complete and the recovery of DY 12 was very effective in the presence of NaCl as an electrolyte. The results showed that up to 600 mg L−1 of DY 12 can quantitatively be removed (>96%) by Cloud point extraction procedure in a single extraction using optimum conditions.